Kewenangan Pemerintah Dalam Melakukan Pengawasan Terhadap Lingkungan Hidup - Nusalawo, Modesta; Sedubun, Victor Juzuf; Holle, Eric Stenly (Faculty of Law, Universitas Pattimura, 2022)
Introduction: provides This study discusses the issue of government authority in supervising the environment.This study discusses the issue of government authority in supervising the environmentPurposes of the Research: The purpose of this study is to identify and analyze the government's authority in the environmental sector and to determine the implementation of the local government's supervisory authority on the environment based on Law Number 11 of 2020 concerning Job Creation.Methods of the Research: This study uses a normative legal research method using a statutory approach and a conceptual approach.Results of the Research: The results and discussion show that the Government based on Article 1 Paragraph (3), Article 71 paragraph (3) and Law No. 32 of 2009 concerning Environmental Protection and Management and Article 72 of Law No. 11 of 2020 on Job Creation, has the authority to carry out supervision of the environment which is the problem used by the author, namely the authority to supervise. The authority for environmental supervision according to Law No. 32 of 2009 includes supervision and the imposition of sanctions. However, the Job Creation Law Number 11 of 2020 specifically regulates, supervises and applies sanctions. The job creation law provides environmental approval, supervision and application of sanctions in the form of direct and indirect warnings, government coercion and does not give authority to local governments in supervising and implementing sanctions.